2003
DOI: 10.1034/j.1600-0609.2003.00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of natural killer (NK) cell activity and adhesion molecules on NK cells from umbilical cord blood

Abstract: The activity of natural killer (NK) cells in human umbilical cord blood (CB) has been reported to be low, compared with that in adult peripheral blood (PB) in vitro. To examine the cause of this, after dividing the CD56+/CD3- cells in CB and PB into CD56bright and CD56dim NK cells, the NK cell activities and the expression of various surface antigens were assayed for each fraction. The NK cell activity of CD56dim NK cells in CB was significantly lower than that in PB (P = 0.0003), whereas, there was no signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
65
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 42 publications
5
65
0
Order By: Relevance
“…In this study, NK cells were purified by negative immunomagnetic selection to prevent any NK cell activation before experiments were undertaken, and a purity Ͼ97% was obtained. In agreement with previous reports (20,22,23,28), the spontaneous cytotoxic activity of CB mononuclear cells against NK-sensitive targets is lower than that of adult mononuclear cells. Our data show that the cytolytic activity of purified CB NK cells is also lower, suggesting that the difference in cytotoxic activity against NK-sensitive targets between CB and adult blood may be attributed to intrinsic differences in NK cells themselves.…”
Section: Cd56supporting
confidence: 81%
See 2 more Smart Citations
“…In this study, NK cells were purified by negative immunomagnetic selection to prevent any NK cell activation before experiments were undertaken, and a purity Ͼ97% was obtained. In agreement with previous reports (20,22,23,28), the spontaneous cytotoxic activity of CB mononuclear cells against NK-sensitive targets is lower than that of adult mononuclear cells. Our data show that the cytolytic activity of purified CB NK cells is also lower, suggesting that the difference in cytotoxic activity against NK-sensitive targets between CB and adult blood may be attributed to intrinsic differences in NK cells themselves.…”
Section: Cd56supporting
confidence: 81%
“…One recent study reported that the expression of adhesion molecules is reduced on CD56 dim CB NK cells (20). However, this study did not investigate the full range of phenotypic and functional markers of NK cell maturation.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…Our findings confirm results from previous studies showing that the CD56 bright CD16 +/2 and CD56 dim CD16 + subsets are present in the same proportions in both CB and PB [33,34]. Nevertheless, these studies also reported that CB NK cells have a natural reduced killing ability as compared with PB NK cells.…”
Section: Discussionsupporting
confidence: 82%
“…Immature NK cell precursors (eg in peripheral blood after allogeneic bone marrow transplantation and in umbilical cord blood) are predominantly CD56 pos /CD16 neg , during NK cell differentiation CD16 expression increases with impact on NK cell functionality. [29][30][31][32][33][34] In all tests, no considerable expression of CD107a was detected on CD56 dim /CD16 pos cells, indicating that these cells do not degranulate in response to NK-sensitive leukemia targets and do not exhibit direct cytotoxicity. Since CD16 surface expression is crucial for antibody-dependent cellular cytotoxicity, it is reasonable that the CD56 dim /CD16 pos cells are the major effector cells mediating this type of cytotoxic response.…”
Section: Discussionmentioning
confidence: 99%